Public confidence in the auditing profession in Singapore - Chu, Stephen Sie Pui (2015)
Public confidence is fundamental for the existence of auditors. Recent spectacular business failures in the US and UK have sparked off a confidence crisis in the auditing profession in these countries. This study addresses the issue of public confidence in Singapore by investigating whether the confidence crisis overseas has proliferated to Singapore. A questionnaire survey of financial and credit analysts and tax assessment officers revealed that the public confidence in Singapore is 3.74 on a scale of 1 to 5. This finding can be adequately explained by the proposed framework of public confidence which comprises five determinants - regulation, auditing methodology, auditors' qualities, expectation gap and recession. The mechanisms of these determinants were illustrated with real world phenomena. Although the empirical study revealed that the auditing methodology and the qualities necessary for conducting an audit in Singapore are considered fairly adequate, expectation gaps with respect to auditors' duties and qualities exist. Finally, potential problems were identified with reference to the framework and several measures were recommended to counteract both existing and potential problems in order to enhance and maintain public confidence in the profession in Singapore. In today's complex and dynamic business environment, the profession must be vigilant and implement appropriate measures to keep itself relevant in order to serve public interests in the best possible manner and maintain public confidence in the profession.